Meta-analyses: Heterogeneity can be a good thing (Past, Present, and Future of Statistical Science, 2014)
Meta-analysis seeks to summarize the results of a number of different studies on a common topic. It is widely used to address important and dispirit problems in public health and medicine. Heterogeneity in the results of different studies is common. Sometimes perceived heterogeneity is a motivation for the use of meta-analysis in order to understand and reconcile differences. In other cases the presence of heterogeneity is regarded as a reason not to summarize results. An important role for meta-analysis is the determination of design and analysis factors that influence the outcome of studies. Here I review some of the controversies surrounding the use of meta-analysis in public health and my own experience in the field.